Processo de elaboração participativa e virtual de um roteiro interpretativo para uma trilha do Parque Ecológico Mico-Leão-Dourado - Bomfim, Lívia de Oliveira (Universidade Federal de São Carlos, 2023)
Interpretive trails are recognized as important strategies for environmental education (EE) actions in natural areas. However, it is common to find interpretive trails built without planning, detached from the local reality, and focused on transmitting information, compromising their educational potential. The present research aimed to create a participatory construction process of an interpretive script for the Viaduto Vegetado Trail of the Parque Ecológico Mico-Leão-Dourado. We structured this process based on participatory approaches and tools, carried out with the team of the Associação Mico-Leão-Dourado and teachers in strategic regions for their actions, in four stages: I) Attractive Survey; II) Interpretive Theme Choice; III) Selection of interpretive points, contents, and strategies; and IV) Presentation and Evaluation of the Script. Except for Stage I, which was carried out in person on the trail with the two participating groups, all stages took place virtually exclusively with the teachers. In addition to producing a script with 14 interpretive points aligned with the expectations of the Park's managers and team and the context in which the trail is inserted, the results of the process demonstrated that this participatory construction process met its objectives. We highlight the main potentialities of the created process: the possibility of reflecting and discussing local environmental issues from the trail space; the engagement of the group in the collective proposal and dialogue as a promoter of knowledge exchange and negotiations among participants. On the other hand, the weaknesses were mostly associated with the challenges imposed by COVID-19, such as the limitations inherent in interactions in virtual participatory methods and the impossibility of validating the construction of the script in person on the trail due to social isolation. Still, some of these weaknesses were mitigated with the use of the Padlet platform for virtual representation of the trail space, which provided a unique description of the use of this platform for the elaboration of interpretive activities. We hope to strengthen participatory approaches for the construction of processes that enhance contextualized and meaningful actions and research for the field of EE.
Participatory and virtual elaboration process of an interpretative script for a trail in the Mico-Leão-Dourado Ecological Park
Keywords: Educação ambiental; Interpretação ambiental; Conservação de fauna; Formação de professores; Environmental education; Environmental interpretation; Wildlife conservation; Teacher training; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM